Factor analysis and evaluation of one-year test-retest reliability of the 33-item Childhood Trauma Questionnaire in Chinese adolescents - Zhang, Jiamei; Wu, Zhipeng; Chen, Min; Gao, Yan; Liu, Zhening; Long, Yicheng; Chen, Xudong (Frontiers in Psychology, 2024)
The 33-item Childhood Trauma Questionnaire (CTQ-33) is a recently developed tool expanded from the 28-item Childhood Trauma Questionnaire (CTQ-28) to assess childhood trauma events, which showed good test-retest reliability over two weeks. However, little is known regarding the factor structure and long-term test-retest reliability of the CTQ-33. To fill such a gap, this study investigated the factorial validity of the CTQ-33 and test-retest reliability of the scale over a relatively long interval of one year. Data on demographics, the CTQ-33 scores, and mental health statuses such as depressive/anxiety symptoms were collected in Chinese adolescents (n = 188) twice across a one-year period. Results of the confirmatory factor analysis (CFA) revealed that the Chinese version of CTQ-33 has close factor validity when compared to the original CTQ-28 in college students. Furthermore, the total and most subscale scores of the CTQ-33 have fair to good test-retest reliability (intra-class correlation coefficients > 0.6 for the total score, and > 0.4 for most subscales), except for the physical abuse subscale. Moreover, we replicated previous findings of significant positive relationships between levels of different childhood trauma subtypes using the CTQ-33. These findings provide initial evidence supporting that the CTQ-33 is overall reliable to assess childhood traumatic events in adolescents over relatively long intervals.